2016
DOI: 10.2217/pgs.15.167
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of DKK1 Polymorphisms in Relation to Skeletal Phenotypes and Bone Response to Alendronate Treatment in Chinese Postmenopausal Women

Abstract: DKK1 polymorphisms may correlate to baseline BMD and serum β-CTX levels, but present a weak effect on the response to alendronate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…However, as we observed in clinic, the efficacy and safety of bisphosphonate were variable. Previous studies reported that the associations between treatment response to alendronate and genetic variants in the candidate gene of the mevalonate pathway 10, the OPG/RANKL/RANK signaling pathway [ 28 ] and the Wnt/β-catenin signaling pathway [ 29 , 30 , 31 ], indicate that interpatient variability could be due to inherited interindividual differences. However, genetic pharmacological studies about bone response to zoledronic treatment are very limited.…”
Section: Discussionmentioning
confidence: 99%
“…However, as we observed in clinic, the efficacy and safety of bisphosphonate were variable. Previous studies reported that the associations between treatment response to alendronate and genetic variants in the candidate gene of the mevalonate pathway 10, the OPG/RANKL/RANK signaling pathway [ 28 ] and the Wnt/β-catenin signaling pathway [ 29 , 30 , 31 ], indicate that interpatient variability could be due to inherited interindividual differences. However, genetic pharmacological studies about bone response to zoledronic treatment are very limited.…”
Section: Discussionmentioning
confidence: 99%
“…77 Many researchers focused on the complex associations between mutations in Wnt pathway genes and bladder cancer, such as secreted frizzled-related protein 1 rs3242. 78 Wang JY et al 79 discovered that Dkk1 rs2241529 correlated to baseline BMD. As emerging molecular biomarkers, some variants of Wnt siganaling pathway genes are in the process of translation to the clinic to help clinical diagnosis and treatment.…”
Section: Wnt Signaling and Diagnosticsmentioning
confidence: 99%
“…Some scholars have detected the coding genes of seven key enzymes in the mevalonate pathway, including Mevalonate kinase (MK), Phosphomevalonate kinase (PMVK), Mevalonate decarboxylase (MVD), Isopentenyl pyrophosphate isomerase (IPI), Geranylgeranyl pyrophosphate synthase 1 (GGPS1), Farnesyl pyrophosphate synthase (FDPS) and Farnesyl-Diphosphate Farnesyltransferase 1 (FDFT1), and three genes of OPG/RANKL/RANK system, a total of 67 tag SNPs, and found that the response to alendronate is significantly associated with the patient's genetic background. [6][7][8][9][10][11] Some enzymes in other pathways of bone metabolism also showed high correlation, such as SOST. 6 Cathepsins are lysosomal cysteine proteases and papain family members.…”
Section: Introductionmentioning
confidence: 99%